Development of a Research-Based E-Module on the Medicinal Plant Kesum (Polygonum minus) as an Antidiabetic for Enrichment of P5 Activities in Senior High School - Herniawati, Herniawati; Hadiarti, Dini; Mukhlishin, Hamdil (Unnes Science Education Journal, 2025)
The implementation of the Merdeka Curriculum at the senior high school (SMA) level emphasizes the execution of the Pancasila Student Profile Strengthening Project (P5), which instills character values and local wisdom. However, the learning modules utilized in P5 typically draw inspiration from online sources and frequently neglect to incorporate local potential. On the other hand, the increasing prevalence of diabetes in Indonesia has become an urgent public health issue, while the use of local medicinal plants such as kesum (Polygonum minus) has not been widely integrated into contextual learning in schools. This study aimed to develop a research-based e-module on the medicinal plant Kesum (Polygonum minus) as an antidiabetic, integrated with the Projek Penguatan Profil Pelajar Pancasila (P5). The development followed the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through teacher interviews and validation by nine experts in content, media, and language. Validation results indicated that the e-module was highly valid for use, with an average score of 86.82%. The practicality of the e-module was tested in a small group trial (1students), yielding a score of 80.75% (practical category), and in a large group trial (60 students), resulting in a score of 82.45% (highly practical category). The e-module was designed to support project-based learning by addressing local issues, strengthening students’ scientific literacy, and promoting local wisdom values. Therefore, this e-module is considered suitable as a contextual learning resource for implementing P5 in senior high schools.